2014
DOI: 10.5301/ejo.5000494
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Intraocular Pressure with Central Corneal Thickness in Premature and Full-Term Newborns

Abstract: Our results showed that the CCT does not affect IOP significantly in preterm infants. More prospective studies are needed for determining the effect of CCT and other ocular and systemic factors on IOP in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In Muslubas’ cohort, CCT changed with birth weight and gestational age. [5] However, Karahan et al [8] found that CCT did not correlate with gestational age or birth weight in their cross-sectional study. The CCT in Sekeroglu et al [13] was negatively correlated with gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In Muslubas’ cohort, CCT changed with birth weight and gestational age. [5] However, Karahan et al [8] found that CCT did not correlate with gestational age or birth weight in their cross-sectional study. The CCT in Sekeroglu et al [13] was negatively correlated with gestational age and birth weight.…”
Section: Discussionmentioning
confidence: 95%
“…Changes in corneal thickness and corneal diameter in premature infants have been observed to occur. [38]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also variable CCT and IOP values of premature infants at the literature [5,7,[9][10][11] The reported differences can be due to timing of evaluation and variable postconceptional ages of infants during measurement. Contrary to aforementioned studies, Muslubas et al [12] found that premature infants have slightly thicker corneas but similar IOP measurements when compared to term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Gunay observed a negative correlation between GA, BW, and CCT in premature infants and demonstrated that GA and BW could significantly predict the CCT values [ 11 ]. However, Karahan et al showed that CCT did not correlate with GA or BW in their cross-sectional study [ 8 ]. Figure 3 in our study showed that the CCT of low BW (≤1500 g) was thicker than high BW (>1500 g).…”
Section: Discussionmentioning
confidence: 99%